Pengembangan Objek Wisata Kilalang Nagari Lubuak Batingkok “Penataan Destinasi Wisata” Kecamatan Harau Kabupaten Limapuluh Kota - Ernawati, Ernawati; Tasrif, Nabila; Budayawan, Khairi; Asnur, Lise; Andres, Fran Serano (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2022)
The Kilalang Nagari Lubuak Batingkok tourist attraction is located in Harau District, Limapuluh Kota Regency, West Sumatra Province. The lack of understanding and skills of the community, product and tourism promotion in structuring tourist destinations is an obstacle in the development of tourist objects at Kilalang Nagari Lubuak Batingkok. This community service activity seeks to increase the ability of the community and be able to innovate in overcoming obstacles to tourism development. The existence of assistance, training and technological guidance is expected to increase the community's ability to manage tourism so that later it can provide a better economic influence on the community.